ANALISIS KEPEGAWAIAN DAN FASILITAS PELAYANAN PULIK DALAM MENINGKATKAN KEPUASAN MASYARAKAT DI PUSKESMAS LESUNG BATU KABUPATEN EMPAT LAWANG - Budiman Sakti (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
The purpose of the study was to determine the effect of employee discipline, work ability and service facilities on the satisfaction of the people who seek treatment at the Lesung Batu Health Center, Lintang Kanan District, Empat Lawang Regency. This research is a quantitative research, with a sample of 100 people. The main tool of data collection is a questionnaire. The analytical tool used to determine the effect of employee discipline, work ability and service facilities on community satisfaction is multiple linear regression. While the hypothesis was tested by t-test (t-test) and F-test (F-test) with 95% confidence level and alpha = 0.05. The results showed that increasing employee discipline, work ability and service facilities could increase the satisfaction of the people who seek treatment at the Lesung Batu Health Center, Lintang Kanan District. Partially, employee discipline, work ability and service facilities have a significant positive effect on the satisfaction of the people who seek treatment at the Lesung Batu Health Center, Lintang Kanan District. Simultaneously, employee discipline, work ability and service facilities have a significant positive effect on the satisfaction of the people who seek treatment at the Lesung Batu Health Center, Lintang Kanan District, Empat Lawang Regency. This means that the previously proposed hypothesis is proven.